(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
The constitutional framework of the European Union (EU) today contains an impressive set of human rights provisions. The treaties declare that the Union is founded on respect for human rights, give a legally binding effect to the EU Charter of Fundamental Rights and authorize the EU’s accession to the European Convention on Human Rights (ECHR). The Treaties require all Member States to accept these values and include a mechanism of sanctions for existing Member States that seriously and persistently violate such rights. Article 19 of the Treaty on the Functioning of the European Union (TFEU) contains the legal basis for a strong EU anti-discrimination regime, while the main basis for the EU human rights framework is Article 6 of the Treaty on European Union (TEU). The purpose of this paper is to present the procedure for EU accession to the ECHR, as well as the latest changes in mutual negotiations. It is an accession that aims to accept the European Union and its institutions as contracting parties against which applications can be filed and proceedings initiated for possible human rights violations provided by the ECHR. The process is long overdue and takes a long time, but should eventually lead to the EU’s eventual accession to the ECHR. The authors of this paper, in addition to explaining the accession procedure, also present their views and opinions regarding further negotiations between the two parties.